Solar energy assessment using moderate resolution remote sensing and GIS-based suitability analysis in the Philippines - Pagba, Cecilia B. (2010)
Availability of solar radiation is part of the fundamental set of information necessary for the development of solar energy applications (e.g., photovoltic & thermal systems). It is therefore imperative to obtain accurate information on available solar energy in any location and time of the year. Currently, solar power industry practitioners in the Philippines are using fixed ground-based instruments such as a pyronometer to measure solar radiation and interpolate the measurements to estimate availability to areas targeted for the solar application. However, incoming solar radiation varies significantly within short extent due to prevailing weather pattern, tapoggraphic heterogeneity and proximity to occlusive features. As an alternative to pyranometer, satelite images may provide wider spatial coverage and cost-effective means to estimate solar radiation. The purpose of this study is to determine availability of solar energy in the Pgilippines using Remote Sensing (RS) and use Geographic Information System (GIS) to determine site suitability considering natural and non-natural factors. The natural factors considered are the amount of solar radiation taht reaches the earth's surface at a given time and location and the Orography (ground elevation, slope gradient and aspect). The non-natural factors are the proximity of target barangays for electrification to potential sites and population as input to the estimation of power demand. For this study, daily images from the Moderate Resolution Imaging Spectrometer (MODIS) acquired for two months were processed using ESRA models with respect to Heliosat method. The satellite-based global horizontal irradiance was used tio generate an hourly radiation with respect to solar zenith angles until an equivalent to 180-degree horizon angles (East to West) are obtained, the hourly duration of direct beam and extinction coefficient. The duration of direct beam was derived using a viewshed analysis and Shuttle radar Topographic Mission Digital Elevation Model (SRTM DEM) as input data. Consequently, global horizontal radiation daily average and monthly average were obtained. This was validated with the ground measurement data from three different sites. Given the spatial coverage limitation, laborious means and costs involved in using pyranometer, the use of satellite image is an excellent and cost-effective alternative. Lastly, a GIS-based suitability was carried to determine the most suitable sites for solar energy systems in the Philippines.
Thesis (M.S. Remote Sensing)--University of the Philippines Diliman
Keywords: Solar energy -- Philippines; Solar radiation -- Philippines; Remote sensing -- Philippines